2004
DOI: 10.1158/0008-5472.can-04-2455
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Regression of Grade 3 Vulvar Intraepithelial Neoplasia Associated with Human Papillomavirus-16–Specific CD4+ and CD8+ T-Cell Responses

Abstract: Cell-mediated immunity directed against human papillomavirus 16 (HPV-16) antigens was studied in six patients affected with grade 3 vulvar intraepithelial neoplasia (VIN3, also known as bowenoid papulosis). Five of the patients presented with a chronic and persistent disease that relapsed after destructive treatments. They showed no detectable anti-HPV blood T-cell responses and no T-cell intraepidermal vulvar infiltrate containing both CD4؉ and CD8؉ lymphocytes. The last patient had a complete clearance of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Likewise, HPV16-induced VIN3 lesions may fail to endow the immune system with strong inflammatory signals and exogenously provided signals will be required to provide a state of inflammation. These signals can be delivered by imiquimod, electrocoagulation (50), or by vaccines (32,33,43).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, HPV16-induced VIN3 lesions may fail to endow the immune system with strong inflammatory signals and exogenously provided signals will be required to provide a state of inflammation. These signals can be delivered by imiquimod, electrocoagulation (50), or by vaccines (32,33,43).…”
Section: Discussionmentioning
confidence: 99%
“…pE7koHBE6-mediated TC-1 protection (Figure 5.3) suggested a role for E6 (EVY)-directed CTL response in pE7HBE6-immunised mice. The importance of a synergistic E6 and E7-directed CTL response may not be clear in these tumour protection experiments; however studies of natural regression of HPV lesions in women (Kadish et al, 2002;Villada et al, 2004;Trimble et al, 2005) and a murine vaccine study (Peng et al, 2006a) have demonstrated enhanced clinical benefits from a combined E6 and E7 CTL responses in control of HPVassociated tumours. Mice bearing TC-1 tumours which were treated with vaccines targeting both E6 and E7 were left with significantly lesser tumour metastases than mice treated with vaccine targeting E6 or E7 alone (Peng et al, 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with responses to both E6 and E7 peptides were 4.4 times more likely to have cleared HPV infection and be CIN negative at a follow-up visit than non-responder patients. In a single patient of a separate study, E6-and E7-directed T-cell responses were associated with regression of vulvar intraepithelial neoplasia-3 lesions (VIN 3), compared to five nonresponders, who did not demonstrate regression (Villada et al, 2004). Women whose HPV-16…”
Section: Regression Of Hpv-associated Neoplasiamentioning
confidence: 95%
See 2 more Smart Citations